Analysis of Alfagift Application User Satisfaction Using the SWOT Method - Syahrul Arya Ramadhan; Jimmie; Syarifah (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
E-commerce has grown tremendously in recent years, with many platforms offering a wide range of products and services. Alfagift, as one of the e-commerce applications, provides convenience for users to shop online with various attractive features, such as promos and discounts. The app is designed to meet the needs of users who want a convenient and efficient shopping experience. This study aims to determine the level of customer satisfaction by using the Swot (Strengths, Weaknesses, Opportunities, Threats) method to evaluate the satisfaction of Alfagift application users. The SWOT method was chosen because of its ability to provide a thorough analysis of internal and external factors that affect user satisfaction, as well as the opportunities and threats that exist in the e-commerce market. From the results of the variance value reliability test, where the score for a positive review value of 4.47 which shows that the user has a very good experience with the use of the alfagift application with a variance value of 0.25, it shows that the score of giving positive reviews has an interesting experience. The calculation of Cronbach's Alpha value obtained was 0.828 which is in the "Good" category and indicates a high reliability instrument, so the data collected can be relied on for further analysis.